HUBUNGAN PENGETAHUAN DOKTER GIGI TERHADAP PENGGUNAAN ALAT PERLINDUNGAN DIRI (APD) DI RUMAH SAKIT ISLAM GIGI DAN MULUT SULTAN AGUNG SEMARANG - Kusuma Arbianti; Meiliana Hanirizqy (Faculty of Dentistry, Universitas Islam Sultan Agung, 2019)
Background: A cross infection is the displacement of the infection agents between patients and health ofcers. Knowledge and behaviors of using personal protective equipment (PPE) are needed to prevent and control the infections. The aim of this study is to fnd out the behaviors of the dentists in using PPE at RSIGM Sultan Agung Semarang.Method: This research is descriptive study using cross sectional approach. There were 19 dentists as the respondents. It was using sampling technique. The data collection was done by providing questionnaire concerning the knowledge and observing the behaviors in using PPE. Statistical analysis used Spearman rho.Result: The Spearman rho test obtained the sig value 0,043 (P<0,05) with a correlation coefcient of 0,469. It can be concluded there is signifcant relationship between the dentist knowledge on the use of PPE at RSIGM Sultan Agung Semarang, with the strength of moderate relationships. Observation results of dentist behavior showed: 42.2% had a moderate category.Conclusion: Thus, it can be concluded that the knowledge is related to dentist behaviors in using PPE is in moderate category. Moreover, the dentist behaviors in using PPE can be inﬂuenced by several factors such as the lack of isolation awareness, the surveillance of Prevention and Control of Infection (PPI), the PPI education and training.